The impact of reduction in intensity of mechanical ventilation upon venovenous ECMO initiation on radiographically assessed lung edema scores: A retrospective observational study - Worku, Elliott T.; Yeung, Francis; Anstey, Chris; Shekar, Kiran (Frontiers in Medicine, 2022)
Background: Patients with severe acute respiratory distress syndrome (ARDS) typically receive ultra-protective ventilation after extracorporeal membrane oxygenation (ECMO) is initiated. While the benefit of ECMO appears to derive from supporting ‘lung rest’, reductions in the intensity of mechanical ventilation, principally tidal volume limitation, may manifest radiologically. This study evaluated the relative changes in radiographic assessment of lung edema (RALE) score upon venovenous ECMO initiation in patients with severe ARDS. Methods: Digital chest x-rays (CXR) performed at baseline immediately before initiation of ECMO, and at intervals post (median 1.1, 2.1, and 9.6 days) were reviewed in 39 Adult ARDS patients. 156 digital images were scored by two independent, blinded radiologists according to the RALE (Radiographic Assessment of Lung Edema) scoring criteria. Ventilatory data, ECMO parameters and fluid balance were recorded at corresponding time points. Multivariable analysis was performed analysing the change in RALE score over time relative to baseline. Results: The RALE score demonstrated excellent inter-rater agreement in this novel application in an ECMO cohort. Mean RALE scores increased from 28 (22-37) at baseline to 35 (26-42) (p<0.001) on D1 of ECMO; increasing RALE was associated with higher baseline APACHE III scores [ß value +0.19 (0.08,0.30) p=0.001], and greater reductions in tidal volume [ß value -2.08 (-3.07,-1.10) p<0.001 ] after ECMO initiation. Duration of mechanical ventilation, and ECMO support did not differ between survivors and non-survivors. Conclusions: The magnitude of reductions in delivered tidal volumes correlated with increasing RALE scores (radiographic worsening) in ARDS patients receiving ECMO. Implications for patient centred outcomes remain unclear, however there is a need to define appropriate ventilator settings on venovenous ECMO, counterbalancing the risks vs. benefits of optimal ‘lung rest’ against potential atelectrauma.